DEOTORISASI PESANTREN DAN KEMASAN BARU NARASI MODERASI BERAGAMA: Studi Kasus Pondok Pesantren Tebuireng melalui Situs tebuireng.online - Faizah, Fatikhatul; Febrianti, Putri (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2023)
This research discusses the typical religious moderation of pesantren. Pesantren as a professional institution that houses of ulama is also responsible for community issues, one of which is religious moderation. Pesantren Tebuireng in this case has deauthorized and expanded to the online realm to take on this role. Through its official website, tebuireng.online, this pesantren produces articles related to religious moderation. To analyse it, the author uses literature-based virtual ethnography and focuses on 14 articles. While the author's findings are that the narrative of religious moderation conveyed remains within the framework of Islam and is typical of Tebuireng Pesantren. The pattern used in making articles is the integration of figural narratives, nationalism, Aswaja. So that the articles produced remain of high quality and maintain the scientific tradition of the pesantren.